AN EXAMINATION OF E-LOYALTY OF INDONESIAN MILLENNIAL TRAVELER ON THE USING OF ONLINE TRAVEL AGENT (OTA) - Pratika, Yeyen; Sutikno, Bayu (PEOPLE: International Journal of Social Sciences, 2017)
Millennial has characteristic of tech-savvy that drives them to use Online Travel Agencies (OTAs) more often. However, another characteristic of millennial is disloyal that becomes a challenge for OTA companies for maintaining their millennial customers. Thus, this study aims to develop and examine a research model that clarifies how millennial travelers become loyal to an online travel agency (OTA). A total of 326 respondents participated in this study. Structural Equation Modeling (SEM) was applied to analyze the research model. Findings indicate that hedonic feature provides significant influence on flow whereas utilitarian feature has significant influence on trust. Furthermore, flow provides significant influence on trust, meanwhile, trust has significant influence on affective and calculative commitment. Lastly, this study confirms that affective and calculative commitment provides significant influence on e-loyalty. The scope of this study is limited to hedonic and utilitarian features of the OTAs that generates experience (flow) and trust of customers, as well as commitment, that will influence millennial traveler’s e-loyalty.